Sistem Panen Kelapa Sawit di Sekunyir Estate, Kalimantan Tengah - Saputra, Aris Adi; Sudradjat (Buletin Agrohorti, 2024)
Palm oil (Elaeis gueenensis Jacq) is an important vegetable oil in Indonesia. Palm oil productivity is influenced by various factors including harvest management. This research had specific objectives to be achieved, namely studying and understanding the management of palm oil harvesting, and analyzing the factors that influence the effectiveness and efficiency of palm oil harvesting. The research was conducted at Sekunyir estate, Central Kalimantan from February to May 2014. Data collection was obtained by direct and indirect methods. Field observations were conducted by following 8 harvesters on the Division of Labour (DOL) system and 4 harvest teams on the 1 Cutter and 2 Carrier (C1R2) system. This research concluded that changing the harvest system from the DOL system to the C1R2 system had a good impact on crop management and the productivity of the harvest team. The C1R2 system had a yield of 5-7% higher than the DOL system in obtaining ripe fruit and had a smaller number of rotten fruits which was around 2.6% compared to the DOL system which reached 8%. Keywords: harvest efficiency, C1R2 system, DOL system, harvesting technique, labor